2017
DOI: 10.1016/j.nicl.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state theta band connectivity and graph analysis in generalized social anxiety disorder

Abstract: BackgroundFunctional magnetic resonance imaging (fMRI) resting-state studies show generalized social anxiety disorder (gSAD) is associated with disturbances in networks involved in emotion regulation, emotion processing, and perceptual functions, suggesting a network framework is integral to elucidating the pathophysiology of gSAD. However, fMRI does not measure the fast dynamic interconnections of functional networks. Therefore, we examined whole-brain functional connectomics with electroencephalogram (EEG) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 57 publications
4
49
2
Order By: Relevance
“…Unthresholded weighted iCoh matrices were used, in line with previous studies (6,(68)(69)(70), where each connection is equivalent to the measured iCoh of two electrodes. Graph-theory metrics measure the degree of network segregation (i.e., the tendency of brain regions to form local clusters with dense functional interconnections), and network integration and efficiency (i.e., the capacity of the network to become interconnected and efficiently exchange information between brain regions) (2,71).…”
Section: Graph-theory Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unthresholded weighted iCoh matrices were used, in line with previous studies (6,(68)(69)(70), where each connection is equivalent to the measured iCoh of two electrodes. Graph-theory metrics measure the degree of network segregation (i.e., the tendency of brain regions to form local clusters with dense functional interconnections), and network integration and efficiency (i.e., the capacity of the network to become interconnected and efficiently exchange information between brain regions) (2,71).…”
Section: Graph-theory Metricsmentioning
confidence: 99%
“…Graph-theory metrics measure the degree of network segregation (i.e., the tendency of brain regions to form local clusters with dense functional interconnections), and network integration and efficiency (i.e., the capacity of the network to become interconnected and efficiently exchange information between brain regions) (2,71). The following commonly-used graph measures were calculated (6,49,69,72,73) correctly-and incorrectly-responded trials in stimulus-locked windows, before target (pre-stimulus; -500-0 ms) and during target processing (post-stimulus; 0-500 ms).…”
Section: Graph-theory Metricsmentioning
confidence: 99%
“…Despite using different methods, other studies have reported that increased theta power and connectivity is related to dysfunctions in affective disorders such as depression, obsessive–compulsive disorder, and posttraumatic stress disorder (Imperatori et al, ; Kopřivová et al, ; Leuchter, Cook, Hunter, Cai, & Horvath, ). Whole‐brain resting‐state theta‐based connectivity is stronger in patients with social anxiety disorders than in healthy controls and is positively associated with state anxiety levels (Xing et al, ). Theta power and coherence increase when an individual engages in personal rumination (Andersen, Moore, Venables, & Corr, ), and increased theta coherence represents attention to negative thoughts or emotions (Xing et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Whole‐brain resting‐state theta‐based connectivity is stronger in patients with social anxiety disorders than in healthy controls and is positively associated with state anxiety levels (Xing et al, ). Theta power and coherence increase when an individual engages in personal rumination (Andersen, Moore, Venables, & Corr, ), and increased theta coherence represents attention to negative thoughts or emotions (Xing et al, ). Especially, significantly decreased theta coherences were observed over medial frontal electrodes centered on Fz (Figure b).…”
Section: Discussionmentioning
confidence: 99%
“…The processes underlying cortical resting-state electrical activity changes in anxious people are actually well understood [3][4][5][6][7][8][9], so are the neurophysiological mechanisms of facial expression recognition in such subjects [10][11][12]. It has been shown that both anxiety and depression, influence recognition of facial expression [13,14].…”
Section: Introductionmentioning
confidence: 99%